1997
DOI: 10.1063/1.364324
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiative decay processes and mechanisms of frequency upconversion of Er3+ in ZrF4–BaF2–LaF3 glass

Abstract: We have investigated the decay processes of the Er:4S3/2 and F39/2 states and the mechanisms of frequency upconversion under 800 nm excitation of Er3+ in ternary ZrF4–BaF2–LaF3 glasses. The decay processes of the Er:4S3/2 and F49/2 states are discussed on the basis of the Er concentration dependence of the fluorescence lifetime. The quantum efficiencies of emission of the S43/2 and F49/2 states are 73% and 25%, respectively. The difference in the quantum efficiencies between these states can be explained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…By excitation of laser in near-infrared wavelength region, all kinds of up-conversion emissions and various energy-transfer processes [1][2][3] have been presented and investigated. Furthermore, the realization of Yb 3+ -sensitized mechanism has made up-conversion efficiency of Yb 3+ -Er 3+ codoped materials improved greatly [4] and the cross-relaxation processes on a single type of Er 3+ ions [5][6][7][8] with a more efficient up-conversion luminescence have been shown in codoped system. More recently, a detailed review involving Er 3+ on up-conversion processes in solid has been reported by Auzel [9].…”
Section: Introductionmentioning
confidence: 98%
“…By excitation of laser in near-infrared wavelength region, all kinds of up-conversion emissions and various energy-transfer processes [1][2][3] have been presented and investigated. Furthermore, the realization of Yb 3+ -sensitized mechanism has made up-conversion efficiency of Yb 3+ -Er 3+ codoped materials improved greatly [4] and the cross-relaxation processes on a single type of Er 3+ ions [5][6][7][8] with a more efficient up-conversion luminescence have been shown in codoped system. More recently, a detailed review involving Er 3+ on up-conversion processes in solid has been reported by Auzel [9].…”
Section: Introductionmentioning
confidence: 98%
“…Hence this wavelength has been chosen as attractive pump wavelength as has been done earlier in other host matrices previously. [18][19][20][21] The dependence of the up-conversion intensity of the composite film with 2 wt.% erbium oxalate content upon baking temperature was examined and the results are depicted in Fig. 7.…”
Section: Experimental Studymentioning
confidence: 99%
“…Neste caso, quanto maior a concentração de íons Er 3+ , maior é a probabilidade de interação entre os mesmos podendo haver transferencia de energia entre eles e assim, o surgimento de um novo meio de decaimento do estado excitado que contribui com uma diminuição no tempo de vida. Esta dependência do tempo de vida do estado 4 S 3/2 com a concentração de Er 3+ é descrita, por exemplo, por Takahashi et al 18 . Um ajuste linear tanto das curvas correspondentes ao sítio 1 (Figs.…”
Section: Espectroscopia Eletrônica De Absorçãounclassified